An anthropologist among the historians and other essays - Cohn, Bernard S., 1928- (Delhi ; New York : Oxford University Press, 1987)
On the civilization and socioeconomic conditions of India; articles.
Includes bibliographies.
Donated by Akbar Ali Khan
Keywords: India -- Civilization; India -- Social conditions